Gerenciamento de resíduos sólidos urbanos: estudo de caso no município de Pato Branco – PR - Starck, Keli (2015)
The solid waste management is a topic much discussed today, this is due to the fact that we have a significant increase in production of solid waste which, when improperly disposed, are polluting sources of air, soil and water. The need to properly manage municipal solid waste evolved quickly and progressively, making it a challenge for society and public administration. In order to contribute to the discussion, this thesis was to analyze the municipal solid waste management process adopted by the city of Pato Branco - PR and its adaptation to the current legislation. This work was methodological basis a case study in qualitative research employing techniques of collecting primary and secondary data. Considering the results obtained through visitation and observation, interviews and questionnaires, it is possible to find what the status of implementation of existing legislation, especially the Política Nacional de Resíduos Sólidos (Law nº 12,305/2010). Despite identify important advances in the city studied, especially in the collection of solid waste and disposal in landfill, there are still two outstanding issues, which relate to remediation of environmental liabilities of the old landfill and performing the composting of organic waste. It points out therefore that the advance in the management of appropriate solid waste is related to the implementation of public policies and the sharing of responsibilities between all actors involved.